No game for boys to play : the history of youth football and the origins of a public health crisis - Bachynski, Kathleen (Studies in social medicine., 2019)
"In 2016, the NFL admitted a link between degenerative brain disease and injuries resulting from tackle football. This admission sparked a new safety debate in professional football. However, the concerns about players' health do not start at the professional level, but at the beginning and intermediate levels of play. In this book, Kathleen Bachynski tells the story of youth tackle football and the debates over player safety in the United States. In the postwar United States, high school football was celebrated as a "moral" sport for young boys, one that promised the creation of the honorable male citizen. However, Bachynski shows that throughout the twentieth century, coaches, sports equipment manufacturers, and even doctors were more concerned with "saving the game" than young boys' safety. By connecting the study of sport, health, childhood, and masculinity, Bachynski shows the social and physical vulnerability of young football players and how commonly held ideas of masculinity shape sport"--